Microbial diversity and chemical analysis of Shuidouchi, traditional Chinese fermented soybean. (February 2019) - Chen, Yu-Hang; Liu, Xue-Wei; Huang, Jia-Ling; Baloch, Saira; Xu, Xin; Pei, Xiao-Fang
Abstract: Shuidouchi is a traditional Chinese fermented soybean product and its quality is largely affected by the microbes involved in the fermentation. In this study, eleven Shuidouchi samples were collected from southwest China and the microbial diversity and its correlations with chemical characteristics were investigated. Bacterial community was detected using 16S rRNA sequencing, along with bacterial and fungal viable plate counts. Biogenic amines and other chemical characteristics were determined by HPLC and corresponding chemical reaction methods. Among eleven Shuidouchi samples, 21 phyla and 356 genera were identified. Firmicutes, Bacteroidetes and Proteobacteria were the predominant phyla while Bacillus, Bacteroides and Lactobacillus were the main genera. The average cell number of bacteria, lactic acid bacteria and fungi were 1.6 × 10 6, 5.9 × 10 4 and 7.6 × 10 3 CFU/g, respectively. HPLC results showed that the mean concentration of tryptamine, β-phenylethylamine, putrescine, cadaverine, histamine, tyramine, spermidine and spermine were 23.11, 3.66, 12.21, 7.12, 8.13, 22.98, 24.72, and 39.00 mg/kg, respectively. The average content of other characteristics including amino acid nitrogen, titratable acidity, and reducing sugar were 2.08, 3.44, and 25.78 g/kg, respectively. Shuidouchi samples were slightly acidic or neutral. Fibrinolytic enzyme activity was detected only in one sample. Among top 52 identified genera, 9 genera showed positive correlations with the chemical characteristics of Shuidouchi while 15 genera were negatively associated. Our results indicated that Shuidouchi contained rich microbial resources and were edible safety based on the tested indexes. The associations identified between microbes and chemical characteristics could be further utilized in the food fermentation industry. Graphical abstract: Unlabelled Image Highlights: First study to describe microbial diversity of Shuidouchi by Illumina Hiseq Sequencing and traditional culture method. Bacterial communities in Shuidouchi are rich and diverse. Some identified bacteria are theoretically of potential utilization in the future fermentation. First study to report the association between microbial diversity and biogenic amines of Shuidouchi. Fibrinolytic enzyme activity was assessed in Shuidouchi.